Toll-like Receptor-4 Polymorphisms and Serum Matrix Metalloproteinase-9 in Newly Diagnosed Patients With Calcified Neurocysticercosis and Seizures. Issue 17 (April 2016) - Lachuriya, Gaurav; Garg, Ravindra Kumar; Jain, Amita; Malhotra, Hardeep Singh; Singh, Arvind Kumar; Jain, Bhawna; Kumar, Neeraj; Verma, Rajesh; Sharma, Praveen Kumar
Abstract : Abstract: We evaluated seizure profile, Toll-like receptor (TLR)-4 polymorphisms, and serum matrix metalloproteinases (MMPs) in patients with calcified neurocysticercosis. One-hundred nine patients with calcified neurocysticercosis with newly diagnosed seizures and 109 control subjects were enrolled. TLR-4 Asp299Gly and Thr399Ile polymorphisms and serum MMP-9 levels were evaluated. The patients were followed for 1 year. Asp/Gly ( P  = 0.012) and Thr/Ile ( P  = 0.002), Gly (Asp/Gly plus Gly/Gly) ( P  = 0.008) and Ile (Thr/Ile plus Ile/Ile) ( P  = 0.003) genotypes were significantly associated with calcified neurocysticercosis compared with controls. Gly/Gly and Ile/Ile genotypes were not significantly associated ( P  = 0.529 for Gly/Gly, P  = 0.798 for Ile/Ile) with either group. The levels of MMP-9 were higher in calcified neurocysticercosis ( P  =  < 0.001). The levels of MMP-9 were higher in patients with multiple calcified neurocysticercosis compared with single calcified neurocysticercosis ( P  =  < 0.001). Headache ( P  = 0.031), status epilepticus ( P  = 0.029), Todd paralysis ( P  = 0.039), lesion size >10 mm ( P  = 0.001), and perilesional edema ( P  =  < 0.001) were significantly associated with seizure recurrence. Heterozygous form Asp/Gly ( P  =  < 0.001) and heterozygous form Thr/Ile ( P  =  < 0.001) were significantly associated with seizure recurrence. The Gly (Asp/Gly plus Gly/Gly) ( P  =  < 0.001) and Ile (Thr/Ile plus Ile/Ile) ( P  =  < 0.001) genotypes were also significantly associated with seizure recurrence. Higher serum MMP-9 levels were significantly associated with seizure recurrence ( P  =  < 0.001). The TLR-4 gene abnormalities may trigger inflammation around calcified neurocysticercosis leading to an increase in perilesional edema and provocation of seizures.